The practice of Islamic work ethic on job performance among employees in Bank Rakyat Penang branches - Mohamad Farizan, Awang Kechik (2018)
Measuring performance is an essential function in business management. Employee performance is a key of a company‟s success. Hence, organizations can achieve of better job performances by attracting employees who already poses the Islamic Knowledge. This study examined the relationship between practices of Islamic work ethic on job performance among employees in Bank Rakyat Penang branches and also to investigate the most significance factor between effort, honesty, teamwork and accountability on job performance among employees in Bank Rakyat Penang branches. It was revealed through previous studies that effort, honesty, teamwork and accountability could be tested in banking sector. The objective of this study is to analyse the major factors that affects the practices of Islamic work ethic on job performance. This study utilised a quantitative method and was carried out specifically in Bank Rakyat at Penang Branches. A total of 137 of the sets questionnaires were successfully collected. The findings of this study showed that there were significant relationship between effort, honesty, teamwork and accountability with the practices of Islamic work ethics on job performance. These findings were great values to both theory and practise and have vital implications for academicians and among banking sectors.